KONFORMITAS MAHASISWA NON MUSLIM KULIAH DI UNIVERSIAS ISLAM NEGERI SULTAN SYARIF KASIM RIAU - Siregar, Monika Rohana; Asriwandari, Hesti (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This study aims to determine the conformity of non-Muslim students studying at the Sultan Syarif Kasim Islamic State University. Where UIN is a university based on the Muslim religion through the pressure that affects it .. Seeing that some of them are non-Muslim students who are studying there with a different ideological basis from those who have to follow rules that are not commonly done before. How do they conform in using K.merton's Anomie theory. This study uses a quantitative research method with a population of 53 non-Muslim students who are at the State Islamic University of Suska Riau. And with a sample of 53 people obtained using a total sample. By taking the entire population. and the data collected is using a questionnaire method and structured interviews. The results of this study indicate that the conformity of non-Muslim students studying at UIN Suska is assessed through factors that influence the level of conformity through: Pressure being a factor affecting the conformity level of UIN Suska students is through the data found that 1.) motivation consists of high self-desire , low parental desire, low follow-up with friends and from low motivation there is no choice. Motivation based on high choice majors. For 2.) interaction consists of low social difficulties, and based on 3.) interaction between dispensation lecturers to memorize high Al-Quran. The level of conformity of UIN Suska students is through the data found that 1.) the achievement consists of academic achievement with high conformity, and through. 2.) learning activities from doing assignments, interest in learning, class attendance, and time obedience with high conformity. And 3.) the level of conformity is based on organizational activities consisting of membership, attendance with low conformity while participating in organizational activities is high. The level of conformity is based on 4.) Ethics and religious courses which consist of complying with a high code of ethics. Keywords: Level of Conformity, Influencing Factor Pressure, Non-Muslim Students.